Position Of Advocate As Law Enforcer In Criminal Trial Process In Indonesia - Aini Hasibuan; Alfina Yanti; Aura Dila; Cindi Puspita; Delta Rika Wijaya; Dwita Khansa; Abdul Halim Nasution (SEAN Institute, 2025)
The purpose of this study is to examine the position of advocates in the criminal justice system in Indonesia. This research is important to do in order to strengthen the legal position of an advocate in the criminal justice system in Indonesia. This study uses a normative juridical research method. This research has novel value because it discusses specifically the position of advocates in the criminal justice system in Indonesia. The novelty of this research lies in the issues discussed specifically the position of advocates in the criminal justice system in Indonesia. Based on the results of the study, it is known that an advocate is part of law enforcement in the criminal justice subsystem in Indonesia. Juridically, the position of an advocate has been contained in the provisions of the Law on Advocates. However, this has not been fully embraced by advocates as law enforcers. There needs to be a clear formulation of the provisions of advocates in law enforcement, especially regarding which institutions are the roofs of advocates as law enforcers.